The Effect of Error Analysis-Based Learning on Proportional Reasoning Ability of Seventh-Grade Students - Khasawneh, Amal Abdallah; Al-Barakat, Ali Ahmad; Almahmoud, Soliman Abedallteef (Frontiers in Education, 2022)
This study investigated the effect of mathematical error analysis-based learning on proportional reasoning ability of seventh-grade students. To achieve the purpose of the study, a proportion unit for the seventh-grade students in Jordan was designed according to the error analysis-based learning. A sample of 45 seventh-grade students participated in the study and were randomly assigned into the following two groups: Experimental group and control group. The data were collected through the following two instruments: A proportional reasoning test and an interview, after ensuring their reliability and validity. The results of the study revealed that the error analysis-based learning led to a significant improvement in proportional reasoning among the experimental group and contributed to providing students with positive experiences in learning mathematics. In light of these results, a set of recommendations for educational researchers, mathematics curriculum designers, and mathematics teachers were presented.